Figures de sages, figures de philosophes dans l'oeuvre de Plutarque - Delfim F. Leão (Classica Digitalia: Humanitas Supplementum - Estudos Monográficos, 2019)
The texts gathered here invite usto approach the work of Plutarch according to thechosen prism: they portray different "figures" accordingto six sections, whichare obviously not without some relations with each other, but whichalso strive when possible todistinguish between"wise" and "philosopher": wisdom and types ofSages; "mythical" figures; the Sage and the politician; figures of philosophers; exemplary figures "in context"; representations and new readings.